Resilient Transport in Small Island Developing States : From a Call for Action to Action - World Bank (Washington, DC: World Bank, 2022)
Small island developing states (SIDS) are among the most exposed, vulnerable countries in the world to natural hazards and the impacts of climate change. SIDS are already experiencing significant economic and social losses from climate change impacts. Extreme weather events such as flooding and hurricanes significantly affect the transport sector, with damage from such events accounting for a large percentage of total infrastructure damage costs. The need for climate adaptation is recognized in SIDS’ nationally determined contributions to the Paris Agreement under the United Nations Framework Convention on Climate Change. The World Bank supports its clients in implementing nationally determined contribution objectives and actions. The World Bank’s programmatic technical assistance, Resilient Transport in Small Island Developing States, implemented with the aim of enhancing the resilience of the transport sector in SIDS, was delivered in three phases. The objective of this report is to help practitioners integrate climate resilience considerations into transport asset management and thus enhance climate resilience in the transport sector of SIDS (Phases 2 and 3 of the technical assistance). The report starts by introducing the topic of natural hazards and climate change in SIDS and how they affect the transport sector. The report describes how governments can develop resilient transport asset management systems (TAMS) and then summarizes the activities implemented in four SIDS, Cape Verde in Africa, Saint Vincent and the Grenadines in the Caribbean, and Solomon Islands and Vanuatu in the Pacific,and shares lessons learned to improve the approach and framework. Finally, the report introduces an online training course on resilient TAMS and the i-Knowledge platform